Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I just ran into the following exercise:

Find and state the convergence properties of the Taylor series for the following: $$\frac{1+z}{1-z}$$ around $z_0=i$.

First of all, let


Then we have that

$$\begin{align} f^{(1)}(z)&=\frac{2}{(1-z)^2},\\ f^{(2)}(z)&=\frac{-4}{(1-z)^3},\\ f^{(3)}(z)&=\frac{12}{(1-z)^4},\cdots \end{align}$$

leading us to conclude that


for $j\geqslant1$. Now, evaluating these at $z=i$ should give the Taylor series


I have two questions: I could derive that same series without problems if the $(-1)^{j+1}$ term were not there, but in this case, where does it go? Also, how does the author determine that this holds whenever $|z-i|<\sqrt{2}$? I suppose that this has something to do with the fact that


converges whenever $|c|<1$. Thanks in advance!

share|cite|improve this question
22 minutes. $ $ – Did Jul 5 '12 at 16:36
Josue, if you dont mind how did you know to put the $i+$ in $i+\sum_{j=1}^{\infty}\frac{2}{(1-i)^{j+1}}(z-i)^j$ also how did you get the $(z-i)^j$ from? – Q.matin Mar 4 '13 at 0:03
up vote 2 down vote accepted

You shouldn't have that alternating sign term showing up. $$f''(z)=\frac{d}{dz}\bigl[2(1-z)^{-2}\bigr]=2\cdot-2(1-z)^{-3}\cdot\frac{d}{dz}[1-z]=-4(1-z)^{-3}\cdot-1=\frac{4}{(1-z)^3}.$$ Something similar will happen in all other cases, too.

It holds whenever $|z-i|<\sqrt{2}$ because the nearest (in fact, only) singularity is the pole at $z=1$. The distance from $i$ to $1$ is $\sqrt{2}$. The radius of convergence of a Taylor series is the distance from the center to the nearest point of nonanalyticity. You can also, of course, see this by rearranging this as a geometric series. Note that $\frac{2}{1-i}=1+i$, so we can rewrite as $$\frac{1+z}{1-z}=i+(1+i)\sum_{j=1}^\infty\left(\frac{z-i}{1-i}\right)^j=-1+(1+i)\sum_{j=0}^\infty\left(\frac{z-i}{1-i}\right)^j,$$ and the series converges for $$\left|\frac{z-i}{1-i}\right|<1,$$ or equivalently, for $$|z-i|<|1-i|=\sqrt{2}.$$

share|cite|improve this answer
You are right! I had forgotten to apply the chain rule thoroughly. Also, I see it now: the pole is at $1$, and $|1-i|=\sqrt{2}$. Thank you! – EsX_Raptor Jul 5 '12 at 16:34

I prefer using geometric series tricks to taking derivatives. Your fraction is $$ \frac{(1+i)+ (z-i)}{(1 - i) - (z-i)}. $$ Using $(1+i)(1-i) = 2$, multiply numerator and denominator by $\frac{1+i}{2}$ to get $$ \frac{\text{stuff}}{1 - \frac{(1+i)(z-i)}{2}} $$ and so the radius of convergence is $|\frac{2}{1+i}| = \sqrt{2}$ (and you get the explicit formula in the usual way if you're less lazy than I am with the numerator).

share|cite|improve this answer

$$ \frac{1+i+u}{1-i-u}=-1+\frac2{1-i}\frac1{1-\frac{u}{1-i}}=-1+\sum\limits_{n=0}^{+\infty}\frac2{(1-i)^{n+1}}u^n,\qquad |u|\lt|1-i|=\sqrt2. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.